Efficiency of application of Trichoderma on the physiological quality and health of cowpea seeds - Reis, Higor Barbosa; Rodrigues, Artenisa Cerqueira; Chagas Junior, Aloisio Freitas; Bonifacio, Aurenivia; Santos, Gil Rodrigues (Comunicata Scientiae, 2019)
One of the main causes of low productivity of cowpea crops in Brazil is the use of low quality seeds. Low quality seeds have a high degree of infestation by phytopathogens, mainly fungi. Seed treatment with biological control agents, such as fungi of the genus Trichoderma, is a useful alternative to reduce or inhibit the transmission of diseases via seeds. In view of the above, this study aims to evaluate the physiological and sanitary quality of cowpea seeds treated with conidia of Trichoderma sp. (1.2, 2.4, 4.8 and 9.6 x 108 CFU g-1). We evaluated the germination and the sanity of seeds, length of seedling radicles, and production of indole acetic acid (IAA) by fungi. The experimental design was completely randomized in all experiments. In general, there was a predominance of Fusarium spp. and Rhizoctonia solani. The treatment of seeds with the conidia of Trichoderma sp. was positive for the parameters related to germination and radicle length of cowpea beans up to the concentration 4.8 x 108 CFU g-1. We conclude that the application of Trichoderma sp. was efficient in reducing the incidence of Fusarium spp., and promoted the germination and elongation of the radicle in cowpea.